A comprehensive review on analytical methods for darifenacin hydrobromide in various Pharmaceutical dosage form - SRUTHI MOHAN, (International Journal of Pharma and Bio Sciences, 2019)
Darifenacin hydrobromide (DHBr), a potent anti-muscarinic agent used in the treatment of overactive bladder. In this review various analaytical methods developed for the quantification of DHBr was studied. The drug acts by relaxing the bladder muscle and it is a selective M3 receptor antagonist. It is a chiral acetate amide tertiary derivative which is marketed as a water soluble hydrobromide salt. The S enantiomer shows the pharmaceutical activity. Numerous analytical methods are available for the quantification of DHBr in various pharmaceutical preparations and in biological fluids. The current review article gives the readers about the various published analytical methodologies of Darifenacin. Most of the researchers made their study in DHBr using the RP-HPLC techniques by using various stationary and mobile phases, these studies also brings about the stability indicating and forced degradation study details of Darifenacin and helps the research scholars and industrialist to gather knowledge about the drug and till now reorganized methods for its determination. Spectrophotometric techniques were also employed widely by the researchers for the study of Darifenacin and the detection was carried out at different wavelengths. Few HPTLC methods were also reported. Finally hyphenated techniques like LC-ESI/MS, HPLC-MS/MS, quantification of Darifenacin in Nano liposomes reported by various researchers were also reviewed. For this review various analytical techniques of Darifenacin were thoroughly touched upon ensuring the research scholars and industrialist an acquaintance of the analytical methods developed, performed and published for DHBr in various journals. The review ensures the research scholars the furtherance in their work in Darifenacin.